Estimating the section elevation angle of cubes on a cubic mesh. Application to nickel microstructure size estimation - Germain, Christian (Image analysis and stereology, 2005)
This paper discusses two new image analysis methods for estimating the elevation angle of the section plane of a material. These methods are applicable to materials such as nickel base superalloys, the microstructure ofwhich shows cubes arranged on a cubic regular grid. 3-D models were proposedthat help interpret the section images and validate our approach. Our first method operates in the Fourier domain, and is based on the estimation ofthe spatial frequencies of the network of lines observed on the section. Thesecond method is based on the average distance measured between hazy areas.Both methods are independent. Applied to synthetic images or to real material samples, they produce comparable estimations. The values of the elevation angle allow us to cancel the bias associated with the estimation of the material pattern dimensions.
Keywords: Nickel; Nikelj; Računalniška simulacija; Alloys; Image Processing, Computer-Assisted; Slika, obdelava z računalnikom; Zlitine; Computer Simulation; nikljeve zlitine; mikrostruktura; analiza slik